The vaginal microbiome in women of reproductive age with healthy weight versus overweight/obesity. Issue 1 (21st November 2021) - Allen, Natalie G.; Edupuganti, Laahirie; Edwards, David J.; Jimenez, Nicole R.; Buck, Gregory A.; Jefferson, Kimberly K.; Strauss, Jerome F.; ,; Wickham, Edmond P.; Fettweis, Jennifer M.
Abstract: Objective: The aim of this study was to evaluate the differences between the vaginal microbiome of reproductive‐aged women with overweight and obesity (Ow/Ob) compared with healthy weight (HW). Methods: In this case‐control study, a cohort of 367 nonpregnant women (18 to 40 years) with Ow/Ob (BMI ≥25 kg/m 2 ) was case‐matched with 367 women with HW (BMI 18.0 to 24.9 kg/m 2 ). The study was a secondary analysis of 16S rRNA vaginal microbiome surveys through the Vaginal Human Microbiome Study (VaHMP). Groups were matched on age, race/ethnicity, income, and nulliparity status. Results: Mean age and BMI of Ow/Ob and HW groups were 26.8 versus 26.7 years and 37.0 versus 22.1 kg/m 2, respectively. The overall vaginal microbiome composition differed between groups (PERMANOVA, p = 0.035). Women with Ow/Ob had higher alpha diversity compared with women with HW (Wilcoxon test, Shannon index p = 0.025; inverse Simpson index p = 0.026). Lactobacillus dominance (≥30% proportional abundance) was observed in a greater proportion of women with HW (48.7%) compared with Ow/Ob (40.1%; p = 0.026). Conclusions: The vaginal microbiome differs in reproductive‐aged women with Ow/Ob compared with women with HW, with increased alpha diversity and decreased predominance of Lactobacillus . Observed differences in the vaginal microbiome may partially explain differences in preterm birth and bacterial vaginosis risk between these populations.